Review of services to inform clinical frameworks for adolescents and young adults with severe, persistent and complex mental illness. (July 2019) - Woody, Charlotte; Baxter, Amanda; Wright, Eryn; Gossip, Kate; Leitch, Elizabeth; Whiteford, Harvey; Scott, James G
Objective: Severe, persistent and complex mental illness (SPCMI) affects a small proportion of young people but is associated with severe disability and a large burden on families and health services. This article identifies and describes service models for adolescents and young adults with SPCMI. Methods: A systematic search was conducted for services for young people aged 12–25 years with SPCMI. The review sought service models providing extended care and/or multidisciplinary services to meet the complex and long-term needs of this population. Results: A total of 43 sources were identified. Evidence of effectiveness was found for both community- and bed-based services. Specific components suggested as important in service delivery included care provided by multidisciplinary teams, consumer and family involvement in care planning, intensive case management and service integration through the continuum of care. Conclusion: Clinical frameworks for this population must incorporate effective community care integrated with inpatient treatment of short duration. Frameworks require consumer and family-centred care with flexibility to support progression through developmental stages and tasks while addressing issues related to risk management, fluctuation in illness severity and stages of recovery. A continuum of care is necessary to meet the needs that arise from SPCMI in adolescents and young adults.